Clivages partisans et partis politiques en Libye - Moncef Djaziri (Revue des Mondes Musulmans et de la Méditerranée)
Libyan society is undergoing rapid socio-economic change which is likely to bring major political change in the medium term. How smooth the upcoming transition will be depends on the role political parties are allowed to play. This article explores the political and party divides in Libya. After a brief, theoretical outline and review of experiments with political parties during the colonial period and in the years following Kadhafi’s rise to power, the study will focus on the organization of contemporary political opposition groups, their similarities and differences. Finally, and with respect to the issue of transition, the article concludes that the institutionalisation of power through Kadhafi’s heirs, seems a reasonable outcome in view of the factors considered. Such a transition will nevertheless have to make allowance for existing cleavages and rely on partisan organizations.